Foreign direct investment in ASEAN and its role in economic growth - Nguyen Phu H.; Rozhanskaya E.A. (Восточная Азия: факты и аналитика)
This paper investigates the role of foreign direct investment (FDI) in fostering economic growth within the ASEAN region, which is a dynamic area known for its fast-paced economic development in recent decades. The study's objective is to analyze the FDI situation in ASEAN and how it is distributed among key sectors such as manufacturing, finance, and trade, as well as to assess the challenges and opportunities that the region faces in attracting foreign capital. The study explores how ASEAN's policies, such as trade liberalization, agreements, the ASEAN Economic Community (AEC), and other initiatives, have successfully positioned the region as a prime destination for FDI. The findings indicate that FDI has significantly contributed to economic growth, job creation, and technological advancement, though benefits remain unevenly distributed among the member states. The paper also highlights the growing importance of sustainable and high-tech investments, emphasizing that future economic progress will require addressing infrastructure gaps, enhancing human capital, and strengthening regulatory frameworks. The findings suggest that, while FDI remains a crucial driver of growth, ASEAN must focus on promoting inclusivity and sustainability in its investment strategies to maintain its competitive edge in the global market.